Assessing plant growth and infection in Avicennia marina (Forssk.) Vierh following inoculation with bacterial endophytes - Savitri, Wina Dian; Askitosari, Theresia Desy (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Endophytic bacteria play an important role for plants in assisting the efficient absorption of nutrients from the surrounding environment. Studies on endophytic bacteria in Avicennia marina plants are still relatively rare. This research aims to determine abilities of three bacterial endophytes and a control Bacillus subtilis infecting the host plant A. marina and conducted in ekowisata mangrove Gunung Anyar, Surabaya. Each endophyte isolates at the concentration of 102, 103, and 104 CFU/mL were used for inoculation, whereas each concentration was applied to 3 plants (triplicate). Every ± 1 m tall A. marina plant was injected with 2 × 500 µL of bacterial solution. Another three plants were chosen and injected with Lactose-Broth (LB) sterile medium. The leaf length and width of 2-4 leaves per plant were measured at day 0 before inoculation and after two weeks of inoculation. Data analysis using paired t-test resulted in no change in leaf area average before and after treatments. Despite the result, we observed that some of the treated plants produced flowers, whereas no flower was observed on control plants. In addition, there were infection zones detected around the infection area. Furthermore, we have observed Indole Acetic Acid (IAA) and siderophore production in all bacterial isolates. The results of this study show that acceleration in the development of A. marina, evidenced by a phase shift from vegetative to generative occurring within a two-week timeframe.